Fighting Viet Cong in the Rung Sat: Memoir of a Combat Advisor in Vietnam, 1968-1969. - Worthington, Bob (McFarland and Company, Inc. : McFarland, 2021)
The Vietnam War was not going well in 1968. The January Tet Offensive--a tactical defeat but strategic victory for North Vietnam--showed the U.S. military and the American public that the enemy remained determined, no nearer defeat. Americans grew war weary while politicians and military leaders could not agree on how to win or how to withdraw. Between combat tours, the author served as a U.S. Army company commander--a job he came to despise. Experiencing what he perceived as a degradation in the Army's senior command, he resigned his commission. Yet he needed money to complete graduate school and volunteered to return to Vietnam as a combat advisor. This memoir describes his participation in the fiercest fighting of the war, on the Cambodian border, where he almost died of hookworm and was shot in a night operation. In Saigon to recuperate, he was tasked with creating an advisory team to train South Vietnamese commandos to conduct raids in the swamps south of Saigon, the Rung Sat Special Zone. For seven months they were successful, with Worthington receiving seven combat decorations.
Keywords: Worthington, Bob, -- 1937-; United States. -- Army -- Officers -- Biography.; United States. -- Army; Vietnam War, 1961-1975 -- Personal narratives, American.; Vietnam War, 1961-1975 -- Campaigns.; Guerre du Viêt-nam, 1961-1975 -- Campagnes et batailles.; Vietnam War.; Military.; HISTORY.; Armed Forces -- Officers; Military campaigns; 1961-1975; Electronic books.; Biographies; Personal narratives -- American